Sense of Ownership: The Leadership Spirit of School Principals Toward Quality and Sustainable Education - Margaretha Dyah Ratna Sari (Journal of Educational Learning and Innovation (ELIa), 2025)
This study aims to explore how a sense of ownership serves as the core of school principals’ leadership in fostering sustainable educational quality. Employing a qualitative approach with a multiple case study strategy based on Eisenhardt’s model, data were collected through in-depth interviews, focus group discussions (FGDs), observations, and document analysis involving three principals within the Seraphine Bakti Utama Foundation. The analysis was conducted through within-case and cross-case stages. Findings reveal that sense of ownership is interpreted as both a strategic and emotional responsibility toward the school, influencing leadership styles, quality improvement strategies, team engagement, openness to critique, and program innovation. The leadership styles that emerged, instructional, participative, and transactional through role modeling, are rooted in a contextual and reflective understanding of ownership. Teacher involvement, impact-based evaluation, and community partnerships were identified as key strategies for building sustainable quality. This study contributes to educational leadership literature by positioning psychological ownership as a foundational driver of contextual and transformational leadership practices. The findings extend the relevance of ownership from corporate settings to the ecosystem of secondary education. Although limited to three cases within private foundation-based schools, the study opens pathways for developing value-based leadership models in broader contexts. Practical implications include strengthening leadership training grounded in reflection and values, as well as policy support that promotes school autonomy and collaborative climates. Future research is recommended to explore diverse educational contexts, including public schools, pesantren, and community-based institutions, using longitudinal approaches to trace the dynamics of ownership in educational leadership.